Design and Realization a New Thermoelectric Sensor, Application - K. Hachami; D. Moussaid; M. Rahmoun; A. El Hassani (Active and Passive Electronic Components)
The present paper deals with design and realization of a New thermoelectric sensor adapted to conceive a circuit breaker, using the thermoelectric effects (Joule, Peltier and Seebeck). The sensor includes two printed circuits. The first is constituted of two resistive tracks of constantan, it is the transmitting circuit. The second, a planar thermoelectric circuit acting as a receiver, is constituted of many plated differential thermocouples. The transmitting circuit is placed on the top surface of the receiver circuit so that the resistive tracks are placed on the levels of thermoelectric junctions. The measuring method consists to passing electrical currents through the resistive tracks in order to generate temperature gradients between junction points of the bimetallic circuit. Then the resulting temperature differences between junction points is directly converted into a proportional Seebeck voltage. As an application, the sensor is adapted to realize a differential circuit-breaker with a low difference current.